Inhibition of histone methyltransferase G9a promotes the osteogenic potential of bone-derived stem cells in diabetic-osteoporosis by regulating the LINC00657/miR-204-5p/IGFBP5 pathway - Mei-qi Qiao; Mei-qi Qiao; Bin Wang; Jian-pin Fan; Feng Gao; Shao-jun Wang; Sheng-yang Guo; Sheng-li Xia; Sheng-li Xia (Frontiers in Endocrinology)
BackgroundBone mesenchymal stem cells (BMSCs) from patients with diabetes often exhibit reduced osteogenic potential. This study aimed to investigate the mechanism of action of G9a, known as euchromatic histone lysine methyltransferase 2 (EHMT2), identify its key responsive long non-coding RNA in diabetic osteoporosis (DOP), and evaluate the effectiveness of the G9a inhibitor (UNC0638).MethodsThe expression level of G9a in bone-derived MSCs (BMSCs) from osteoporosis patients with or without T2DM (T2DM-BMSCs, CON-BMSCs) was detected, and osteogenic differentiation was evaluated by osteogenic genes, ALP activity and calcification level. The key lncRNA, LINC00657, was screened based on previous transcriptome sequencing, qPCR and gene overexpression assay. The downstream miRNA and the target gene of LINC00657 were identified through transcriptome sequencing, bioinformatics analysis, dual luciferase reporter assay and gene overexpression assay. Rat DOP was constructed, and micro-CT, histochemical staining, immunofluorescence and qPCR were used to investigate the mechanism of UNC0638.ResultsG9a expression was increased and LINC00657 expression was decreased in T2DM-BMSCs, compared with CON-BMSCs. UNC0638 treatment improved the osteogenic potential of T2DM-BMSCs and reversed the downregulation of LINC00657. LINC00657 overexpression reverses the inhibitory effect of EHMT2 on osteogenic differentiation. miR-204-5p and IGFBP5 were screened as downstream molecules of LINC00657. LINC00657 was able to sponge miR-204-5p and upregulated IGFBP5 expression, thereby promoting osteogenesis in T2DM-BMSCs. UNC0638 treatment alleviated osteoporosis in DOP rats, whereas LINC00657 knockdown inhibited its effect in vivo.ConclusionsG9a inhibits the osteogenic potential of T2DM-BMSCs by regulating the LINC00657/miR-204-5p/IGFBP5 pathway and UNC0638 may be a potential agent for DOP treatment.